Osakkeenomistajien nimitystoimikunta - Salminen, Lassi (Lakimies, 2024)
Shareholders’ nomination board The shareholders’ nomination board is a typical way to prepare shareholder proposals regarding the board for the general meeting. It is not a recognised body under the Companies Act but rather a local Nordic governance arrangement described in self-regulation and established by the decision of the general meeting. The nomination board organises the largest shareholders of the company and unites their decision-making under a unified and coordinated operation, thereby institutionalising the exercise of control by the controlling shareholders. The nomination board can be considered an agent for other shareholders. In self-regulation, specifics are left to be determined in company-specific terms, within the limits set by company law. The formulation of recommendations has led to varying practices in companies. The position and role of the nomination board are influenced by company-specific regulations and ownership structures.